New records of bats (Mammalia: Chiroptera) from Cu Lao Cham and Ly Son archipelagos, central Vietnam - Thong, Vu Dinh; Loi, Dao Nhan; Luong, Nguyen Thanh; Huy, Hoang Quoc; Thanh, Hoang Trung (Academia Journal of Biology, 2019)
Cu Lao Cham and Ly Son are two well-known archipelagos of Vietnam for their specular landscapes and varied ecosystems including forest, cave, and agriculture. However, their bat fauna has received little attention. Between July 2017 and August 2018, we conducted a series of mammal surveys with emphasis on bats of the two archipelagos. Bats were captured by mist nets and harp traps. Echolocation calls of microchiropteran species were recorded using the PCTape system then analysed by Selena software. With reference to all available literatures and specimens from the recent surveys, we obtained confirmed records of 9 bat species from Cu Lao Cham and 3 species from Ly Son. Of these, Megaderma spasma and Taphozous melanopogon are new to Cu Lao Cham while Rhinolophus macrotis is new to Ly Son. These three species were rarely recorded from other islands of Vietnam and also uncommon within Cu Lao Cham and Ly Son. These new records not only expand the known distributional range, but also provide worthwhile notes on a narrow geographical variation in morphology and echolocation of each species.